Comparative of the Results of the Throw-net Catch at Different Mesh Sizes in Kerinci Lake - Bandi, Zikri Naqsa; Lisna, Lisna; Mulawarman, Mulawarman (Fakultas Perikanan dan Kelautan Universitas Riau, 2021)
Nets are a simple fishing tool which principally confines fish so they cannot escape. The mesh sizes that are often used by the people of Kerinci Lake are the mesh sizes of 2.5 inches and 4.5 inches. The research objective was to compare the catch of jala lempar with mesh sizes of 2.5 inches and 4.5 inches in Kerinci Lake. The method used is the experimental fishing method by catching 16 trips. The results showed that the catch of jala lempar with a mesh size of 2.5 inches got a catch with a weight of 53.930 kg and a total of 266 fish, while a 4.5 inch mesh size obtained a catch with a weight of 33.844 kg and a total of 51 fish. the type of fish that you get is tilapia and barau. The use of different mesh sizes on the Net fishing gear shows a significant difference (P <0.05) to the weight of the catch, at mesh size 2.5 inch, with an average catch weight of 3.371 kg while the mesh size is 4.5 inches. obtained an average catch weight of 2.111 kg. Based on this research, it can be concluded that using a 2.5 inch mesh size results in more catch than 4.5 inches in size